Recent advancements of polysaccharides to enhance quality and delay ripening of fresh produce: a review - Wen, Felicia Xia Ling; Kobun Rovina; Md Nasir Nur’Aqilah; Joseph Merillyn Vonnie; Kana Husna Erna; Mailin Misson; Nur Fatihah Abdul Halid (MDPI, 2022)
The freshness of fruits and vegetables plays a significant role in consumers’ decision to purchase a product at the supermarket. Fresh-cut products are the latest trend in fulfilling society’s restless needs, and the food industry is faced with the challenge of maintaining the quality of fresh produce. The food industry is concerned with the natural maturation and degradation of fruits and vegetables, primarily due to enzymatic reactions. It has been demonstrated that polysaccharide coatings effectively preserve the freshness of these products, extending their shelf life depending on the preservation method used. This review informs readers about the different types of polysaccharides and their novel applications as natural food preservatives in the past five years (2018–2022). The key findings summarized the properties of the antimicrobial agent, the molecular mechanism of action, coating methods, and formulation for the preservation approach. Additionally, we discuss the scientific factors influencing polysaccharide processing and preservation efficacy, allowing it to be used in post-harvest management